Wartość zapasów produktów gotowych według znowelizowanej ustawy o rachunkowości a wskaźniki finansowe - Kowalak, Robert (Stock Value of Products in the Accountacy Act and Financial Ratios, 2005)
Changes in the Accountancy Act related to calculating the cost of producing a product affect stock level and financial results. It means that financial ratios are based on these economic categories can show different value in relation to previous periods. Changes have caused also new possibilities for creating new ratios that could be used by analysts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 348-355